2013
DOI: 10.1038/ajg.2013.104
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for the Development of Nonalcoholic Fatty Liver Disease in a Nonobese Chinese Population: the Zhejiang Zhenhai Study

Abstract: NAFLD is prevalent in the nonobese Chinese population, and a substantial proportion of subjects developed NAFLD over the 5-year follow-up period. Special attention should be paid to the factors associated with the presence and development of NAFLD in nonobese subjects, to improve prevention and management of NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
152
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(165 citation statements)
references
References 31 publications
6
152
1
6
Order By: Relevance
“…Risk factors for the development of NAFLD were assessed in a subsequent prospective study in NAFLD-free individuals at baseline, 494 of who had developed NAFLD during the 5-year followup. Prevalence of NAFL was found to be 7.27% [9] .…”
Section: Epidemiologymentioning
confidence: 99%
“…Risk factors for the development of NAFLD were assessed in a subsequent prospective study in NAFLD-free individuals at baseline, 494 of who had developed NAFLD during the 5-year followup. Prevalence of NAFL was found to be 7.27% [9] .…”
Section: Epidemiologymentioning
confidence: 99%
“…29,34 Increasing age may also impact the risk of NASH and fibrosis, but data on sex are, again, inconsistent. Middle-aged and elderly individuals have a higher prevalence of fibrosing NASH.…”
Section: 15mentioning
confidence: 99%
“…[21][22][23][24][25][26] Other studies, although confirming that men are at higher risk of NAFLD, have shown an inverse association between NAFLD and age. [27][28][29][30] Conversely, in women, advancing age, menopausal status and MetS features are all independent predictors of NAFLD. 31,32 The lower prevalence of NAFLD which has been reported with advancing age in the elderly, 33 is potentially attributable to either selective mortality or development of cirrhosis (which generally loses steatosis).…”
Section: 15mentioning
confidence: 99%
“…In addition, our study showed involvement of other factors which have also been proposed as indices of oxidant stress status, namely serum hemoglobin levels were significantly and independently associated with GGT activity (inversely) and albumin concentration (positively), while OC correlated with bilirubin level. Hemoglobin [116,117], albumin [118][119][120] and bilirubin [118,121] exhibit potent antioxidant properties. Increases in GGT activity may reflect the responses of counteracting mechanisms to protect against oxidative damage.…”
Section: Potential Mechanisms: Combining Regulatory Elementsmentioning
confidence: 99%